“We were locked in with our trauma” - a mixed-methods study of health pathways among intimate partner violence (IPV) survivors during COVID-19 lockdowns in Ontario - Idriss-Wheeler, Dina; El-Khatib, Ziad; Hancock, Lauren; Ham, Marlene; Bainbridge, Shannon; Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background The COVID-19 pandemic disproportionately affected certain populations, with intimate partner violence (IPV) survivors facing heightened risks of adverse health outcomes. This study examined whether women who experienced IPV during Ontario’s COVID-19 lockdowns were more likely to report negative behavioural, psychological, and physiological health outcomes compared to women who did not experience IPV . Methods Using a convergent mixed-methods design, a cross-sectional survey of Ontario residents and semi-structured interviews with key stakeholders were conducted. The final sample comprised 653 survey respondents who identified as women, 23% of whom reported experiencing IPV during COVID-19 lockdowns (n = 150). A total of 24 interviews were conducted, including 14 IPV survivors and 10 violence against women (VAW) service providers. Results Quantitative findings revealed that IPV survivors had significantly higher odds of adverse behavioural outcomes, including increased alcohol (43.3% vs. 21.9%, RRR = 3.39, p < 0.001), tobacco (15.3% vs. 8.8%, RRR = 2.16, p = 0.014), cannabis (23.8% vs. 10.4%, RRR = 3.49, p < 0.001), and illicit substance use (6.8% vs. 0.6%, RRR = 14.31, p < 0.001), as well as greater decreases in sleep quality (61.4% vs. 40.3%, RRR = 3.24, p < 0.001). They also exhibited more polarized help-seeking patterns: increased reliance on formal supports (34.7% vs. 12.9%, RRR = 4.75, p < 0.001) and higher likelihood of decreased informal support (29.5% vs. 17.3%, RRR = 2.53, p = 0.001). Logistic regression further supported that IPV survivors had over twice the odds of reporting poor mental health (aOR = 2.46, 95% CI: 1.27–4.75) and nearly twice the odds of poor physical health (aOR = 1.84, 95% CI: 1.00–3.36). Qualitative insights revealed that structural barriers, trauma, stigma, and loss of autonomy contributed to these adverse outcomes. Conclusions These results underscore the bidirectional relationship between mental and physical health and the compounded vulnerabilities exacerbated by crisis conditions. Findings highlight the need to integrate IPV considerations into emergency preparedness and response planning to ensure continuity of care for IPV survivors. As public health emergencies and climate disasters become more frequent, inclusive responses must prioritize those most at risk, including IPV survivors.